"Sexuality, Women, and Tourism. Cross-border desires through contemporary travel", de Susan Frohlick. - López-Ruiz, Mauricio (Universidad de Costa Rica, 2014)
Reseña del libro Sexuality, Women, and Tourism. Cross-border desires through contemporary travel, de Susan Frohlick.